Quick comments from participants on the Food Nutrition in Eastern and Southern Africa Workshop, September 2012 - International Livestock Research Institute (International Livestock Research Institute, 2012)
A food nutrition in eastern and southern Africa workshop was co-hosted in Nairobi on 10–11 Sept, 2012 by the Australian International Food Security Centre and the International Livestock Research Institute to define research priorities for Australian investments in food and nutritional security in sub-Saharan Africa.